2014
DOI: 10.1186/s12933-014-0153-4
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide can inhibit calcification of human VSMCs through the NF-kappaB/RANKL signaling pathway

Abstract: BackgroundArterial calcification is an important pathological change of diabetic vascular complication. Osteoblastic differentiation of vascular smooth muscle cells (VSMCs) plays an important cytopathologic role in arterial calcification. The glucagon-like peptide-1 receptor agonists (GLP-1RA), a novel type of antidiabetic drugs, exert cardioprotective effects through the GLP-1 receptor (GLP-1R). However, the question of whether or not GLP-1RA regulates osteoblastic differentiation and calcification of VSMCs h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 43 publications
0
20
0
2
Order By: Relevance
“…В работе Jun-Kun Zhan и соавт. [23] изучалось влияние агониста рецептора ГПП-1 на па-тогенетические звенья, лежащие в основе кальцификации сосудистой стенки. Исследование показало, что агонист рецептора ГПП-1 обладает зависимым от дозы ингибиру-ющим влиянием на активность β-глицеролфосфата, по-тенцирующего дифференциацию остеобластов и кальци-фикацию сосудистых ГМК, а также лиганда-рецептора активатора ядерного фактора каппа-В (Receptor Activator of NF-κB Ligand-RANKL), являющегося мощным стиму-лятором минерализации сосудистых ГМК [23].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…В работе Jun-Kun Zhan и соавт. [23] изучалось влияние агониста рецептора ГПП-1 на па-тогенетические звенья, лежащие в основе кальцификации сосудистой стенки. Исследование показало, что агонист рецептора ГПП-1 обладает зависимым от дозы ингибиру-ющим влиянием на активность β-глицеролфосфата, по-тенцирующего дифференциацию остеобластов и кальци-фикацию сосудистых ГМК, а также лиганда-рецептора активатора ядерного фактора каппа-В (Receptor Activator of NF-κB Ligand-RANKL), являющегося мощным стиму-лятором минерализации сосудистых ГМК [23].…”
Section: Discussionunclassified
“…[23] изучалось влияние агониста рецептора ГПП-1 на па-тогенетические звенья, лежащие в основе кальцификации сосудистой стенки. Исследование показало, что агонист рецептора ГПП-1 обладает зависимым от дозы ингибиру-ющим влиянием на активность β-глицеролфосфата, по-тенцирующего дифференциацию остеобластов и кальци-фикацию сосудистых ГМК, а также лиганда-рецептора активатора ядерного фактора каппа-В (Receptor Activator of NF-κB Ligand-RANKL), являющегося мощным стиму-лятором минерализации сосудистых ГМК [23]. Исследо-вательские работы в данном направлении продолжаются, но и в настоящее время имеющиеся данные указывают на широкий терапевтический потенциал и разнообразие благоприятных эффектов агонистов рецептора ГПП-1, что, возможно, будет способствовать пополнению списка показаний к применению препаратов этой группы.…”
Section: Discussionunclassified
“…Osteocalcin concentration significantly increases during calcification and arterial calcification is an important complication of diabetes due to the differentiation of vascular smooth muscle cells into osteoblast-like cells. Although some work demonstrates an inhibitory effect of GLP-1RAs on vascular calcifications, this is not always the case (Zhan et al 2014, Davenport et al 2015.…”
Section: Osteocalcinmentioning
confidence: 97%
“…5 Vascular calcification and other dysfunctions of the middle vascular membrane are closely related to VSMC phenotypic conversion, transdifferentiation and apoptosis. 6,7 Some studies have demonstrated that exosomes play an important role in angiogenesis, vascular calcification and senescence of VSMCs. [8][9][10][11] By transferring information among cells, exosomes in cellular senescence processes can regulate cell-cell communication.…”
Section: Introductionmentioning
confidence: 99%